Unsolved Issues of Atherosclerosis Prevention and of Adequate Lipid-lowering Therapy in Patients with Acute Ischemic Cerebrovascular Accident - S. A. Boytsov; M. A. Piradov; M. M. Tanashyan; I. A. Voznjouk; M. V. Ezhov; E. V. Oschepkova; I. V. Sergienko; N. A. Shamalov; S. N. Yanishevskiy (Рациональная фармакотерапия в кардиологии, 2022)
The existing system of medical care for patients with acute cerebrovascular accident of atherothrombotic genesis, namely lipid metabolism disorders, the modern evidence base for lipid-lowering therapy in this category of patients and the feasibility of interdisciplinary interaction of cardiologists and neurologists were discussed at a meeting of the expert council of cardiologists and neurologists in Moscow on 2021 July 7.